Development and characterization of EST‐SSR markers in Asarum sakawanum var. stellatum and cross‐amplification in related species. Issue 3 (22nd December 2016) - Takahashi, Daiki; Sakaguchi, Shota; Setoguchi, Hiroaki
Abstract : EST‐SSR markers were developed for A sarum sakawanum var. stellatum to evaluate the genetic diversity and genetic structure of series S akawanum and assess their utility in other series in the genus Asarum . A total of 1864 primer pairs, including 1864 tri‐nucleotide SSR motifs, were designed based on transcriptome data. Of the 96 primers tested, 17 loci were successfully amplified and polymorphic in series S akawanum taxa. Furthermore, all these loci were successfully amplified in A. takaoi, whereas only 10 loci were amplified in the more phylogenetically distant A . pellucidum . For populations of A . sakawanum var. stellatum, the values of observed and expected heterozygosity ranged from 0.261 to 0.957 and 0.317 to 0.881, respectively. These newly developed EST‐SSR markers will be used in population genetic studies of series S akawanum to infer the evolutionary history and genetic diversity of these series, many of which are endangered in Japan. Abstract : Polymorphic EST‐SSR markers were developed for series S akawanum (genus Asarum ) to investigate its population genetics.